Assessment of disturbed voltage supply effects on steady-state performance of an induction motor - Jamal Abdul-Kareem Mohammed; Sahar R. Al-Sakini; Arkan Ahmed Hussein (Institute of Advanced Engineering and Science, 2020)
An electric power system is usually exposed to unequal and variable loads across its three phases, which leads to voltage unbalance and variation, making the three-phase voltages asymmetrical in nature at the distribution end. This problem is clearly evident in Iraq country, particularly with regard to the fluctuating voltage levels of electricity distribution during peak hours. Providing a three-phase motor with asymmetric voltages is badly affecting its working performance. Estimating the performance of this motor at steady-state under different conditions of voltage disturbances is investigated in this paper through Matlab simulation using Symmetrical component approach. The motor performance represented by active and reactive input powers, output put power, developed torque, power losses, efficiency and power factor is analyzed under full load conditions. Also, the steady-state power losses- and torque-slip characteristics at certain degrees of voltage unbalance have been calculated and plotted